2021
DOI: 10.7759/cureus.17848
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Adaptation for Multidisciplinary Colorectal Cancer Clinic During the COVID-19 Pandemic

Abstract: BackgroundThe study objectives were to transition in-person colorectal cancer multidisciplinary clinic (MDC) to a telehealth MDC (tele-MDC) format and to assess early outcomes. MethodsA colorectal tele-MDC was devised, in which patients used remote-access technology while supervised by a clinician. The team consisted of surgeons, medical oncologists, radiation oncologists, radiologists, and pathologists. Outcomes were assessed with patient and provider surveys, using a 5-point Likert scale (higher = more favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Telehealth in cancer care delivery, or tele-oncology, refers to the delivery of clinical oncology services through audio and video communication platforms to remote patients including chemotherapy monitoring, pain and symptom management, and palliative care [ 6 ]. In addition to the benefit of reducing infection risk during the COVID-19 pandemic, patients with cancer and treating physicians have reported general satisfaction with telehealth use in cancer care delivery [ 7 - 10 ]. However, challenges associated with telehealth remain, such as patient access to technology, quality of communication, establishing rapport between a physician and a new patient, and reimbursement policies [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth in cancer care delivery, or tele-oncology, refers to the delivery of clinical oncology services through audio and video communication platforms to remote patients including chemotherapy monitoring, pain and symptom management, and palliative care [ 6 ]. In addition to the benefit of reducing infection risk during the COVID-19 pandemic, patients with cancer and treating physicians have reported general satisfaction with telehealth use in cancer care delivery [ 7 - 10 ]. However, challenges associated with telehealth remain, such as patient access to technology, quality of communication, establishing rapport between a physician and a new patient, and reimbursement policies [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies suggest telehealth in oncology patients is convenient, may improve access to speci c services such as medication renewals and/or adjustments, specialty consultations and education or counselling services [18,19], whereas other studies have suggested challenges with clinical effectiveness of telehealth, especially with respect to evaluation of new medical concerns and di culty building provider-patient rapport [18,20,21]. The ideal strategy to effectively engage and deliver telehealth supportive care services remains unknown, although there is some data to suggest telehealth may serve as an effective adjunct in the care of cancer survivors [19,[22][23][24]. Through an anonymous survey, we assessed the telehealth experiences of pediatric CNS tumor survivors and caregivers in our multidisciplinary program.…”
Section: Introductionmentioning
confidence: 99%